2020
DOI: 10.1038/s41418-020-0569-1
|View full text |Cite
|
Sign up to set email alerts
|

Olig2 SUMOylation protects against genotoxic damage response by antagonizing p53 gene targeting

Abstract: Posttranslational modifications of nuclear proteins, including transcription factors, nuclear receptors, and their coregulators, have attracted much attention in cancer research. Although phosphorylation of oligodendrocyte transcription factor 2 (Olig2) may contribute to the notorious resistance of gliomas to radiation and genotoxic drugs, the precise mechanisms remain elusive. We show here that in addition to phosphorylation, Olig2 is also conjugated by small ubiquitin-like modifier-1 (SUMO1) at three lysine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 67 publications
(129 reference statements)
0
18
0
Order By: Relevance
“…An important pathway enriched with linseed supplementation is the P53 signaling pathway, which is involved in damage repair and cell proliferation [ 46 ]. Some of the up-regulated genes ( APAF3, CCNG1, CCNG2 and PPM1D ) are intermediates for P53 activity, which is involved in cellular growth arrest, apoptosis, angiogenesis and DNA repair [ 47 ]. Our data demonstrated that linseed supplementation promotes mammalian anti-cancer activity as reported in previous studies [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important pathway enriched with linseed supplementation is the P53 signaling pathway, which is involved in damage repair and cell proliferation [ 46 ]. Some of the up-regulated genes ( APAF3, CCNG1, CCNG2 and PPM1D ) are intermediates for P53 activity, which is involved in cellular growth arrest, apoptosis, angiogenesis and DNA repair [ 47 ]. Our data demonstrated that linseed supplementation promotes mammalian anti-cancer activity as reported in previous studies [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, even in the absence of p53, cancer cells are still able to halt cell cycle in response to genotoxic stimuli [ 180 , 181 ]. It was shown that in response to chemotherapeutic agents, cell cycle arrest and apoptosis are p73 dependent [ 71 , 156 , 157 , 182 ].…”
Section: P73 and Hallmarks Of Cancermentioning
confidence: 99%
“…In fact, p53 is an excellent target as public neoantigen, considering that it is by far the most frequently mutated gene [31][32][33][34] and it has roles in regulating crucial factors in cancer biology such as cell death [35][36][37][38][39], cell cycle [40], cell metabolism [41][42][43][44][45][46][47][48], as well as commensal microbes [20,[49][50][51]. This is in keeping the function of the other members of the same family, namely p63 and p73 [52][53][54][55][56][57][58][59]; and with the ability to predict overall cancer patient survival [60][61][62] as other prognostic factors in cancer progression [27,63,64].…”
Section: Bispecific Antibodies As An Innovative Cancer Immunotherapymentioning
confidence: 99%